Analysis of the Diagenetic Fluid of Deep Dolomitic “Leopard-Spot” Limestones in the Middle Permian Qixia Formation in Shuangyushi Region in Northwest Sichuan Basin, China - Xie, Shengyang; Wang, Xingzhi; Li, Bo; Jiang, Hang; Du, Yao; Zhang, Rui; Li, Yong; Wei, Mingyang; Huang, Dong; Kang, Jiahao; Zhang, Benjian; Huo, Fei (Frontiers in Earth Science, 2022)
A thorough investigation of the characteristics and formation mechanism of dolomite is of great significance to assess the validity of dolomitization theory and dolomite reservoirs. Extensive development of dolomites has been found in the organic bank of the Middle Permian Qixia Formation in the northwest of the Sichuan Basin. For that reason, field profile and drilling core samples were collected from the common dolomitic “leopard-spot” limestones in the Middle Permian Qixia Formation in the study area and observed in this work. The diagenetic fluid and formation factors of dolomites were analyzed through major elements, microelements, carbon, oxygen and strontium (Sr) isotope, and fluid inclusion as well as order degree of dolomite. From the extracted outcomes valuable insights can be derived. More specifically, in the study area, dolomitic “leopard-spot” limestones were mainly developed in the upper part of Section II in the Qixia Formation. It is interesting to notice that the vertical distribution plays a dominant role since it was transited gradually and gently to the thick-layered lumpy crystalline dolomites downward. The dolomitic “leopard-spots” are mainly composed of dolosiltite-fine crystalline dolomites with residual fabrics and the base limestones were mainly formed by biomicrites (debris). In addition the average δ13C of dolomitic “leopard-spot” and base limestones was 3.06‰ and 3.31‰, respectively; whereas their average δ18O was -4.29‰ and -3.16‰ and the 87Sr/86Sr (0.70734 in average) was higher than those of the contemporaneous seawater and mantle provenance range. Moreover, the contents of the major elements in dolomitic “leopard-spots” and base limestones were basically consistent. The uniform temperature of inclusion ranges between 70 ℃ and 115 ℃. According to the geochemical data and the previously reported studies on the regional paleogeotemperature environment, the diagenetic fluid of the dolomitic “leopard-spot” limestones in the Qixia Formation in the northwest Sichuan Basin was mainly attributed to contemporaneous sea flows. However, influenced by the local high-temperature environment, the terrestrial atmosphere and the fresh water, it is speculated that the dolomitic “leopard-spot” limestones in the study area might belong to dolomitization involving fresh water from the penecontemporaneous stage to the early shallow burial stage.